Regional disparities in subjective wellbeing across Europe: A fuzzy hybrid TOPSIS approach - Alessandro Indelicato; Juan Carlos Martín; Vincenzo Marinello (PLoS ONE, 2026)
The study analyses differences in subjective well-being (SWB) across European regions. Through the Fuzzy-Hybrid TOPSIS approach, we analyse SWB at the country and regional levels. Additionally, a quantile regression model is employed to investigate the impact of socio-economic factors on SWB. The International Social Survey Programme (ISSP) dataset from 2017 is used for seven countries: Denmark, Germany, Spain, France, Finland, Hungary and Slovenia. The synthetic indicator is derived from four indicators: happiness, life satisfaction, goal achievement, and family pressure. At the country level, Germany achieves the highest SWB score (0.69), while Hungary records the lowest (0.51). Regional analysis shows German regions (particularly Saarland and Schleswig-Holstein) and Spanish regions (notably La Rioja and Baleares) occupy top positions in the SWB rankings. Quantile regression results confirm that age, education level, and income significantly influence SWB, with older individuals, those with intermediate education levels, and higher-income earners showing consistently higher SWB values.